2005
DOI: 10.1104/pp.105.063164
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Engineering of the Biosynthesis of Glycinebetaine Enhances Photosynthesis against High Temperature Stress in Transgenic Tobacco Plants

Abstract: Genetically engineered tobacco (Nicotiana tabacum) with the ability to synthesis glycinebetaine was established by introducing the BADH gene for betaine aldehyde dehydrogenase from spinach (Spinacia oleracea). The genetic engineering enabled the plants to accumulate glycinebetaine mainly in chloroplasts and resulted in enhanced tolerance to high temperature stress during growth of young seedlings. Moreover, CO 2 assimilation of transgenic plants was significantly more tolerant to high temperatures than that of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
108
1
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(119 citation statements)
references
References 67 publications
8
108
1
2
Order By: Relevance
“…It is possible that the extreme-temperature tolerance induced in transgenic Arabidopsis is due to the protection of Rubisco activase by GB. This finding was further supported by the increased photosynthetic activity in BADH-transgenic tobacco (Yang et al 2005). The physiological basis for the enhanced tolerance of growth to high-temperature stress (25-45°C) in transgenic tobacco might be associated with an increased tolerance of photosynthesis to high temperatures.…”
Section: Gb Protects Photosynthesis Against Heat Stresssupporting
confidence: 67%
See 2 more Smart Citations
“…It is possible that the extreme-temperature tolerance induced in transgenic Arabidopsis is due to the protection of Rubisco activase by GB. This finding was further supported by the increased photosynthetic activity in BADH-transgenic tobacco (Yang et al 2005). The physiological basis for the enhanced tolerance of growth to high-temperature stress (25-45°C) in transgenic tobacco might be associated with an increased tolerance of photosynthesis to high temperatures.…”
Section: Gb Protects Photosynthesis Against Heat Stresssupporting
confidence: 67%
“…The physiological basis for the enhanced tolerance of growth to high-temperature stress (25-45°C) in transgenic tobacco might be associated with an increased tolerance of photosynthesis to high temperatures. Moderately high temperatures do not affect the activity or efficiency of PSII, and the enhanced CO 2 assimilation rate induced by GB is associated with the Rubisco activase-mediated activation of Rubisco (Yang et al 2005). The accumulation of GB increases the tolerance of Rubisco activase to high temperatures that results in enhanced tolerance of CO 2 assimilation in transgenic plants as compared to the wild type controls.…”
Section: Gb Protects Photosynthesis Against Heat Stressmentioning
confidence: 88%
See 1 more Smart Citation
“…Overproduction of glycinebetaine also provided significant advantage to the growth of young transgenic seedlings at supra-optimal temperature in this study. Yang et al (2005) overexpressed betaine aldehyde dehydrogenase protein from spinach into tobacco plants, to increase glycinebetaine levels. Tobacco transformants in this study showed increased thermotolerance in terms of growth of young seedlings as well as CO 2 assimilation rates.…”
Section: High Temperature Tolerant Transgenics Raised Through Alterinmentioning
confidence: 99%
“…In contrast to each of these two pathways that involved two enzymes, the biosynthesis of GB is catalysed by a single flavoenzyme choline oxidase (COD) in certain microorganisms such as the soil bacterium Arthrobacter globiformis (Ikuta et al, 1977). To achieve tolerance against various abiotic stresses, overexpression of BADH (Moghaieb et al, 2000;Kumar et al, 2004;Yang et al, 2005), CDH (Lilius et al, 1996;Quan et al, 2004) has been carried out in several plant species. Overexpression of coda gene encoding COD has been most widely attempted to develop abiotic stress tolerant transgenic plants (Hayashi et al, 1997;Alia et al, 1998;Huang et al, 2000, Sulpice et al, 2003Parvanova et al, 2004;Prasad and Pardha-Saradhi, 2004).…”
Section: Targeting Osmotic Homeostasis Machinerymentioning
confidence: 99%